Cultura Viva: serie documental de la comunidad nativa Kichwa Wayku - Olaya Fernández, Edwin Raúl (2023)
This documentary project Cultura Viva has been carried out in the Kichwa Wayku Native Community of the district and province of Lamas, and whose main objective is to promote and disseminate the Cultural Identity of the Kichwa-speaking family. The project consists of the production of a series of mini documentaries with a duration between 5 to 7 minutes and will be published on the social networks of YouTube, Facebook and Instagram. The first chapter entitled "The loss of the Kichwa Lamisto" is already published on the official pages, which has generated a lot of interest and concern among viewers to continue learning about and encouraging the cultural traditions of this original group. The population of the Wayku Native Community is currently in a process of acculturation with respect to its cultural identity, which has descendants from the Chancas and Pocras. The young generations have put aside their ancestral customs such as language, clothing and the typical celebrations of their community, which represents them as a folkloric city. It has been observed that they are ashamed to speak their native language and prefer to communicate in Spanish, allowing the integration of modern Western culture; so this is totally harming their original culture. All this allows us to reflect on the social problems that the Wayku Native Community lives with the loss of its cultural traditions and with this audiovisual project it is intended to contribute to the improvement and cultural, social and economic takeoff of the aforementioned community.